2017
DOI: 10.1016/j.stemcr.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Naive-like ESRRB+ iPSCs with the Capacity for Rapid Neural Differentiation

Abstract: SummarySeveral groups have reported the existence of a form of pluripotency that resembles that of mouse embryonic stem cells (mESCs), i.e., a naive state, in human pluripotent stem cells; however, the characteristics vary between reports. The nuclear receptor ESRRB is expressed in mESCs and plays a significant role in their self-renewal, but its expression has not been observed in most naive-like human induced pluripotent stem cells (hiPSCs). In this study, we modified several methods for converting hiPSCs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The naive human and marmoset PSCs we recently reported (Kisa et al, 2017;Shiozawa et al, 2020) were characterized by the strong expression of ESRRB, which has an important role for the maintenance of the naive pluripotent state in murine ESCs (Festuccia et al, 2012). However, when utilizing the medium for inducing these naive human PSCs in this study, the primary dome-shaped colonies that initially appeared after the transfection of fibroblasts (Figures 1B, 1D, 6B, and 7A) were not naive or primed-state PSCs (Nichols and Smith, 2009), but were presumably NSC-like cells, as shown through multiple analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The naive human and marmoset PSCs we recently reported (Kisa et al, 2017;Shiozawa et al, 2020) were characterized by the strong expression of ESRRB, which has an important role for the maintenance of the naive pluripotent state in murine ESCs (Festuccia et al, 2012). However, when utilizing the medium for inducing these naive human PSCs in this study, the primary dome-shaped colonies that initially appeared after the transfection of fibroblasts (Figures 1B, 1D, 6B, and 7A) were not naive or primed-state PSCs (Nichols and Smith, 2009), but were presumably NSC-like cells, as shown through multiple analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the conventional method for generating hiPSCs (Okita et al, 2011) was not applicable to marmoset cells. Next, we decided to utilize a medium we previously reported for inducing and maintaining putative naive-state hiPSCs and marmoset ESCs from conventional primed-state cells (termed as NSM) (Kisa et al, 2017;Shiozawa et al, 2020). Using NSM as the induction medium, we observed primary dome-shaped colonies from both E01F and E02M embryonic fibroblasts 30 days after transfection (Figure 1B, left).…”
Section: Derivation Of Primary Colonies From Marmoset Fibroblasts Using Episomal Vectorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased neuroectodermal and reduced meso-and endodermal differentiation bias combined with low lineage marker expression at pluripotency are features reported for naive mouse (Marks et al, 2012) and naive human (Kisa et al, 2017;Lee et al, 2017) pluripotent stem cells (PSCs). We thus asked whether the presence of those features in E8 hPSCs could reflect a differential pluripotency state.…”
Section: E8 Hpscs Display Enhanced Pluripotency Features and Expression Of Naive Markersmentioning
confidence: 99%
“…However, the human cells have gene regulatory networks that utilize KLF5, KLF7, TFCP2L1, FOXR1, ZIC2, and TFAP2C, for the naïve state; and OTX2 and SALL2 for the primed state ( Takashima et al, 2014 ; Weinberger et al, 2016 ; Pastor et al, 2018 ). Some of these are active in mouse naive mESCs (KLF5 and TFCP2l1); however, several seem unique to humans (e.g., TFAP2C), and some critical regulators in mice (e.g., Esrrb ) are not typically upregulated in human naïve cells ( Kisa et al, 2017 ; Rostovskaya et al, 2019 ). Consequently, there are substantial differences in transcriptional regulation in humans ( Table 2 ), and the full naïve and primed regulatory networks remain to be elucidated.…”
Section: Naïve and Primed States In Humansmentioning
confidence: 99%